(untitled) (University of Khartoum Engineering Journal, 2022)
The main objective of this study to investigate the effectiveness of the gravity concentration technique for beneficiation of the low-grade chromite ore materials after the high-grade lumps are sorted out by hand picking from the run of mine ore. They are low-grade type of ore containing a high amount of fine serpentine as gangue materials, and an average chromium oxide content of about 21.56 % Cr2O3. Based on the fact that there are significant differences in specific gravity between the desired chromite mineral and the gangue minerals, therefore it was suggested that gravity separation methods may be able to concentrate this type of ore .This technique was attempted to process Ingassana waste materials within mine dumps. The chromite mineral of this sample could be liberated at around 500um. Such material size would be successfully dressed by gravity processes. Hence, these materials were subjected to treatment by heavy media system .The heavy medium separation has produced from the treated materials concentrate of about46.5 %Cr2O3 and a recovery of about 85.48%Cr2O3 are achieved.